Pharmacological and Nursing Perspectives on the Management and Counseling of Individuals with Sickle Cell Trait - Arishi, Abdulghafur Abdu A; Alfarhan,WaleedIbrahimAli; Alshehri, Hind Mohammed Ghaythan; Al-Qarni, Abdullah Mohammed Bariq; Safta, Ghaida Adel; Mahnashi, Samirah Ali Ali; Albahuth,ThekraBandarKhalid; Almotairy, Ayed Shabeeb Sh; Alhuzari,MunirahAyedhAbdullah; Shammari, Naif Mdhi Rafa Al; et al. (Saudi Journal of Medicine and Public Health, 2024)
<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; vertical-align: baseline; white-space-collapse: preserve;">Background:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; vertical-align: baseline; white-space-collapse: preserve;"> Sickle cell trait (SCT) is a common inherited hemoglobin variant, traditionally considered a benign condition. It is caused by heterozygosity for the hemoglobin S (HbS) gene. While most carriers are asymptomatic, emerging evidence indicates that specific physiological stressors can unmask serious complications. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; vertical-align: baseline; white-space-collapse: preserve;">Aim:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; vertical-align: baseline; white-space-collapse: preserve;"> This article synthesizes the current understanding of SCT, aiming to clarify its pathophysiology, epidemiology, and potential health risks. It seeks to outline best practices for the management, counseling, and interdisciplinary care of individuals with SCT to prevent morbidity and mortality. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; vertical-align: baseline; white-space-collapse: preserve;">Methods:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; vertical-align: baseline; white-space-collapse: preserve;"> A comprehensive review of SCT was conducted, encompassing its genetic etiology, pathophysiology of sickling under stress, and epidemiological distribution. The evaluation and management strategies are detailed, including laboratory diagnosis, differential diagnosis, patient education, and the specific roles of pharmacists and nurses in an interprofessional team. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; vertical-align: baseline; white-space-collapse: preserve;">Results:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; vertical-align: baseline; white-space-collapse: preserve;"> Under conditions like dehydration, hypoxia, or extreme exertion, individuals with SCT are at risk for complications including exertional rhabdomyolysis, renal papillary necrosis, hematuria, splenic infarction, and thromboembolic events. While life expectancy is normal, targeted education and preventive strategies are crucial to mitigate these risks. Effective management hinges on genetic counseling, especially for reproductive planning, and proactive surveillance for renal and exertional issues. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; vertical-align: baseline; white-space-collapse: preserve;">Conclusion:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; vertical-align: baseline; white-space-collapse: preserve;"> SCT is not a benign state but a condition with conditional risks. A proactive, interprofessional healthcare approach is essential for patient education, complication prevention, and genetic counseling to improve outcomes.